Clinical, radiological, and pathological features of 33 adult unilateral thalamic gliomas. Issue 1 (December 2016) - Zhang, Peng; Wang, Xingchao; Ji, Nan; Xie, Jian; Han, Jinsong; Ren, Xiaohui; Song, Guidong; Wu, Ruofei; Zhang, Liwei; Gao, Zhixian
Abstract Background Unilateral adult thalamic gliomas are rarely reported. In this study, the authors aimed to analyze the clinical, radiological, and pathological features of adult primary unilateral thalamus gliomas (UTGs). Methods Clinical data of 33 UTGs in adults who underwent surgical treatment between 2005 and 2014 at the Beijing Tiantan Hospital were collected and retrospectively studied. Follow-up evaluation was performed. Results This study included 21 males and 12 females with a mean age of 43.1 years. The most common symptoms were headache (75.8 %, 25/33 patients) and motor deficits (42.4 %, 14/33 patients). Radiological results showed that enhancement was common (90.9 %, 30/33 patients) and included cystic appearances in 9 cases (27.3 %). All patients underwent maximal safe tumor resection. Gross total resection (GTR) was achieved in 19 cases, subtotal resection (≥80 %) in 9 cases, and partial resection (<80 %) in 5 cases. Molecular pathology results were available in 15 cases. After surgery, 25 patients received postoperative adjuvant therapy based on the remaining pathology. The median follow-up period of all 33 patients with UTGs was 17 months (1 week~49 months). Twenty-four patients experienced tumor recurrence. The 1-year and 2-year progression-free survival (PFS) rates were 49.0 and 10.2 %, respectively. The 1-year and 2-year overall survival (OS) rates were 68.1 and 25.9 %, respectively. Survival analyses revealed that several predictive factors were correlated with better prognosis, among which, GTR and tumor with cystic appearances were significantly associated with a longer survival. Conclusions Adult UTGs displayed a wide spectrum of clinical features. GTR can be achieved in adult UTGs with acceptable complications and conferred a better prognosis. Tumor with cystic appearance may indicate better prognosis. More patients and longer follow-up periods are needed to further elucidate the biological features of adult UTGs.